Effect of different conditions of growth and storage on the cell counts of two lactic acid bacteria after spray drying in orange juice - Barbosa, Joana (2016)
Consumers increasingly require innovative food products with health benefits. Thus, a dried orange juice incorporating probiotics could be a novel challenge. In this context, we investigated whether different sugars added to the culture media used for growth of two lactic acid bacteria contributed to their protection during spray drying in orange juice and subsequent storage under different conditions of temperature, light exposure and water activity. Cell viability during passage through simulated gastro-intestinal conditions was also investigated. Cells grown in culture medium containing fructose resulted in the worst survival rates during storage. High survival was observed for cells grown in the presence of lactose, followed by glucose. The survival of dried bacteria was enhanced at 4 C, water activity of 0.03 and absence of daylight. For cells grown in standard culture medium and after 12 months of storage at 4 C in orange juice powder (about 109 cfu/mL), there was a reduction of approximately 2 log-units for both lactic acid bacteria after gastro-intestinal tract passage simulation. Using the conditions of growth and storage investigated, it is possible to improve the survival rate of lactic acid bacteria and produce an orange juice powder with probiotic characteristics with shelf life of at least 12 months.